Tuberculosis drug resistance in Canada, 1998 to 2000 - Melissa D Phypers (Canadian Journal of Infectious Diseases, 2001)
The emergence of drug-resistant strains of tuberculosis (TB) is a global threat to TB prevention and control efforts. A recent study conducted by the World Health Organization (WHO) and the International Union Against Tuberculosis and Lung Disease found strains of TB resistant to first-line anti-TB drugs in all countries surveyed (1). The WHO estimates that 50 million people are infected with strains of drug-resistant TB (2).